تحديد صوارف الأمر عند الأصوليين وأثره في اختلاف الفقهاء - Sha'ib Muhammad Wani (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study aims to elucidate one of the Usuli themes, which is strongly related to the Arabic language. The theme is positive command and its distracting tools (al-Amr wa Sawarifuhu). This imperative command is regarded as one of the types of specific expression (khass) by the jurists. Hence it is part of linguistic themes in the science of Usul al-Fiqh. The researcher has given a definition of the positive command, lexicographically and technically; thereby selecting the most preponderant definition. In addition, he has discussed formula of the positive command, important issues related thereto, and different implications of the positive command. He has also given definition of the distracting tools (sarif) lexicographically and technically, explained types of contextures (Qaraʼin), distracting tools that are devoid of contextures and restrictive distracting tools for the positive command. Finally, the researcher has discussed the impact of the distracting tools for the positive command on disagreement among the scholars in jurisprudential issues, with a particular reference to selected matters concerning worship, financial transactions, and personal law. For this study, the researcher has used descriptive and analytical methods. Some findings of the study include the fact that there is disagreement among the jurists on definition of the positive command and the most preponderant one is this: demanding an action through an expression from a posture of superiority; the most preponderant view regarding the implication of the positive command that is devoid of contexture is that it indicates an obligation; and the distracting tools for the positive command are many, unlike the position of the Zahiri scholars who limited them to the text (al-Nass) and consensus (al-Ijmaʼ) only. It has become clear that disagreement regarding determining the distracting tools for the positive command has led to disagreement on Shari'ah rules of many jurisprudential issues. In most instances, the disagreement is always between the majority scholars and the Zahiri scholars.